Ionic liquid/water mixture promoted organic transformations. Issue 63 (10th July 2015) - Reddy, Pedavenkatagari Narayana; Padmaja, Pannala; Subba Reddy, Basireddy V.; Rambabu, Gundla
<x xml:space="preserve">Abstract</x> Wet ILs constitutes a new class of solvents with their own new and interesting properties. The IL–water mixing makes it easy to control the properties of the solution and the formation of these ionic liquid mixtures increases synthetic flexibility.